Combination of pelvic floor and abdominal muscle exercises to reduce perineum pain in postpartum mothers - Ulfah, Mariah; Novitasari, Dwi; Murniati, Murniati (Universitas Muhammadiyah Purwokerto, 2019)
Background: Perineum Pain risks a lack of rest time which will affect the reduction in milk production and can interfere with the process of uterine contractions which further risks the occurrence of subinvolution. Previous studies have only examined pelvic floor muscle exercises, however, they have not been combined with abdominal exercise. The combination of abdominal muscle exercises can increase the effectiveness of pelvic floor muscle performance so that it will improve blood circulation and make muscles relaxed and inhibit the increase in lactic acid due to muscle spasms and ischemic tissue that makes pain.Objective: To find out the benefits of a combination of Pelvic Floor Muscle and Abdominal Muscle Exercises to Reduce Perineum Pain in Postpartum MothersMethods: This is a pre-experimental research with one group pretest-posttest design. The sample used was 16 people with random techniques. Statistical analysis was done by Wilcoxon while pain measurement was done by VAS instrument.Results: The results showed the mean of the pain before doing the exercise was 3.94 and the mean of the pain after doing exercise was 1.62. From statistical test results by Wilcoxon test, it obtained a significance value of 0.003 (p <0.05). Thus it was concluded that there were significant differences in perineum Pain before and after Pelvic Floor and Abdominal Muscle ExercisesConclusion: Combination of pelvic floor muscle exercise and abdominal muscle can reduce perineum pain in postpartum mothers.